Modelling the impact of exchange rate risks on imports / Azlina Hanif and Noor Zahirah Mohd Sidek - Hanif, Azlina; Mohd Sidek, Noor Zahirah (2012)
Risks arising from the exchange rate can be divided into two major categories - exchange rate volatility and exchange rate misalignment. The primary reasons why exchange rate risks are of interest to policymakers are due to the fact that: (I) Risks emanating from exchange rate volatility may increase or reduce the cost of imports and , (2) Exchange rate undervaluation may result in higher cost of import and overvaluation of the exchange rate may suppress costs of imports. Existing studies focus on the impact of exchange rate volatility on imports (see for example Koray and Lask"apes, 1989; Klein, 1990; Cushman, 1988) but to the best of our knowledge, the impact of exchange rate misalignment on imports has yet to be studied. The prime objective of this study is to develop a theoretical model, which explains the relationship between exchange rate risk and imports. Subsequently, the impact of exchange rate risks on imports will be examined using this model. We also examine whether exchange rate risks affects the performance of imports at both aggregated and disaggregated level. Both short and long run behavior will be examined using the estimation method proposed by Pesaran et al. (2001 ). The impact of shocks in exchange rate risks on imports will be simulated based on the impulse response and variance decomposition techniques. We expect the results to support our hypothesis that exchange rate volatility depresses import activities . Exchange rate misalignment in the form of undervaluation is expected to increase the cost of imports hence discourages imports and overvaluation is expected to confer an opposite effect i.e. reduces the cost of imports hence promote import activities. Asymmetries in the events of overvaluation and undervaluation are also suspected. That is, the magnitude of percentage increase (decrease) in imports as a result of exchange rate overvaluation (undervaluation) is expected to differ.